Defect Characteristics of Reverse Hill-Sachs Lesions. (March 2016) - Moroder, Philipp; Tauber, Mark; Scheibel, Markus; Habermeyer, Peter; Imhoff, Andreas B.; Liem, Dennis; Lill, Helmut; Buchmann, Stefan; Wolke, Julia; Guevara-Alvarez, Alberto; Salmoukas, Katharina; Resch, Herbert
Background: Little scientific evidence regarding reverse Hill-Sachs lesions (RHSLs) in posterior shoulder instability exists. Recently, standardized measurement methods of the size and localization were introduced, and the biomechanical effect of the extent and position of the defects on the risk of re-engagement was determined. Purpose: To analyze the characteristics and patterns of RHSLs in a large case series using standardized measurements and to interpret the results based on the newly available biomechanical findings. Study Design: Case series; Level of evidence, 4. Methods: In this multicenter study, 102 cases of RHSLs in 99 patients were collected from 7 different shoulder centers between 2004 and 2013. Patient- as well as injury-specific information was gathered, and defect characteristics in terms of the size, localization, and depth index were determined on computed tomography or magnetic resonance imaging scans by means of standardized measurements. Additionally, the position (gamma angle) of the posterior defect margin as a predictor of re-engagement was analyzed. Results: Three types of an RHSL were distinguished based on the pathogenesis and chronicity of the lesion: dislocation (D), locked dislocation (LD), and chronic locked dislocation (CLD). While the localization of the defects did not vary significantly between the subgroups ( P = .072), their mean size differed signficantly (D: 32.6° ± 11.7°, LD: 49.4° ± 17.2°, CLD: 64.1° ± 20.7°; P < .001). The mean gamma angle as a predictor of re-engagement was similarly significantly different between groups (D: 83.8° ± 14.5°, LD: 96.5° ± 17.9°, CLD: 108.7° ± 18.4°; P < .001). The orientation of the posterior defect margin was consistently quite parallel to the humeral shaft axis, with a mean difference of 0.3° ± 8.1°. Conclusion: The distinction between the 3 different RHSL types based on the pathogenesis and chronicity of the defect helps identify defects prone to re-engagement. The gamma angle as a measurement of the position of the posterior defect margin and therefore a predictor of re-engagement varies significantly between the defect types.